The effect of centella asiatica ethanolic extract on caspase-3 expression in prefrontal cortex of chronic restraint stress induced sprague dawley rat - Kuswati Kuswati (Faculty of Medicine, Universitas Islam Indonesia, 2015)
Introduction: Stress cause changes in the structure and function of the prefrontal cortex. Chronic restraint stress causes the shortening of dendrites in the medial prefrontal cortex. Centella asiatica is an herb that has antioxidant and neuroprotective effects. The purpose of this study is to understand the effect of Centella asiatica on the active protein caspase-3 apoptosis executor expression in the prefrontal cortex. Methods: This study was a laboratory experimental using posttest only control group design. The study used 25 pieces of stored biological material sample in the form of rat brain tissue paraffin blocks. These brain tissues came from 25 rats that were divided into groups of P1, P2, P3, P4 and P5. P1 group treated with restraint stress. Group P2, P3 and P4 were subjected to restraint stress and Centella asiatica ethanolic extract with therapeutic dose of 150, 300 and 600 mg/kg/day. P5 group received stress treatment and fluoxetine with therapeutic dose of 10 mg/kg/day. On the 23rd day, termination, perfusion and brain tissues sampling were executed. Furthermore, the brain tissues were made into paraffin blocks, cut into specimen, immunohistochemical stained, and count the cells which were expressing active caspase-3. Results: There were significant differences in the expression of active caspase-3 between P1 to P2, P3, P4 and P5 groups (p = 0.00). There were no significant differences between P2, P3, P4 and P5 groups. Conclusion: Centella asiatica ethanolic extract can inhibit active caspase-3 expression in the prefrontal cortex of Sprague Dawley rats that were induced with chronic restraint stress.